Organic materials for proton exchange membranes: Structure and transport properties - Nuha, Awang; Azyyati, Johari; Mohd Al-Fatihhi, Mohd Szali Januddi; Aliff Radzuan, Mohamad Radzi; Hazlina, Junoh; Nurasyikin, Misdan; Norazlianie, Sazali (Wiley, 2025)
This comprehensive review explores the intricate interplay of molecular structure, morphology, and chemical composition in proton exchange membrane (PEM) design, with a focus on enhancing performance for fuel cells and electrolyzers. The discussion encompasses advancements in polymer synthesis, polymer blending, nanomaterial integration, and the challenges associated with maintaining PEM stability. Researchers have strategically incorporated functional groups like sulfonic acid, phosphonic acid, carboxylic acid, and hydroxyl into polymer backbones to optimize transport properties. Polymer blending, involving combinations like sulfonated aromatic polymers with hydrocarbon-based polymers, showcases a balance between mechanical strength and proton conductivity. Nanomaterials, including titanium dioxide, graphene, and carbon nanotubes, revolutionize PEM design, offering innovative solutions for improved morphology and performance. Despite these advancements, challenges in chemical and mechanical stability persist. The review emphasizes the necessity for interdisciplinary collaboration, material innovations, and evolving technologies, underscoring the ongoing quest for durable and efficient PEMs in various electrochemical applications.